JHS 2021
DOI: 10.12658/m0631
|View full text |Cite
|
Sign up to set email alerts
|

How Does Paternalistic Leadership Affect Employees’ Work Engagement? The Mediating Roles of Workaholism and Trust-in-Leader

Abstract: In this study, we contend that paternalist leadership can be an effective way of managing people and can pave the way for employee motivation and well-being, despite several previous studies linking it to adverse outcomes. In addition, we propose two possible underlying mechanisms (i.e., workaholism, trust in leadership) linking a leader’s paternalistic style to employee work engagement. By doing so, we aim to understand whether paternalist leaders positively influence their subordinates through a social conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
3
0
1
Order By: Relevance
“…Confirming the previous research on the impact of different leadership typesnamely transformational leadership (Y. Li, 2019), servant leadership (Zhou et al, 2022), paternalistic leadership (Koçak & Küçük, 2021), engaging leadership (Rahmadani et al, 2020;W. Schaufeli, 2021)-on WE, we have found that DL of school principals have a significant effect on teachers' WE.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Confirming the previous research on the impact of different leadership typesnamely transformational leadership (Y. Li, 2019), servant leadership (Zhou et al, 2022), paternalistic leadership (Koçak & Küçük, 2021), engaging leadership (Rahmadani et al, 2020;W. Schaufeli, 2021)-on WE, we have found that DL of school principals have a significant effect on teachers' WE.…”
Section: Discussionsupporting
confidence: 89%
“…As indicated in the job demands-resources theory (Bakker & Demerouti, 2007), leadership is a critical job resource producing positive teacher behaviors and attitudes such as WE. Recent studies on WE also support the positive link between different leadership types and WE (Bakker & Demerouti, 2007;Decuypere & Schaufeli, 2020Koçak & Küçük, 2021;Zhou et al, 2022). On the other hand, leadership not only supports the employees' positive attitudes towards their work but is also a significant variable in shaping their relationship with their administrator.…”
Section: Distributed Leadership Work Engagement and Trust In Principalmentioning
confidence: 84%
See 1 more Smart Citation
“…Studi terbaru tentang work engagement mempunyai hubungan yang positif antara kepemimpinan dengan work engagement (Decuypere, A., & Schaufeli, 2020;Demerouti, 2007;Kocak, O., & Kucuk, 2022;Subekti, 2022;Zhou, G., Gul, R., & Tufail, 2022). Di sisi lain, kepemimpinan tidak hanya mendukung sikap positif guru terhadap pekerjaan mereka, tetapi juga merupakan faktor penting yang dapat mendukung work engagement yang menunjukkan bahwa perilaku kepemimpinan yang positif dapat membangun kepercayaan karyawan terhadap pemimpinnya (Burke et al, 2007;Goodwin et al, 2011;Kocak, O., & Kucuk, 2022) Profesi guru telah diakui sebagai salah satu profesional berisiko tertinggi di dunia (Dupriez, 2016), sehingga keadaan di lapangan guru sering menghadapi tugas yang berat dan mengalami stress yang tinggi karena guru harus berurusan dengan pekerjaan administratif, sejumlah pekerjaan rumah, tekanan waktu dan target-target sekolah, masalah disiplin, tekanan dan kritik dari orang tua siswa. Semua keadaan ini mempengaruhi work engagement guru yang berdampak pada efektivitas guru dalam menjalankan tugasnya (Iancu, 2018;Redin & Garce, 2020;Taris, 2017).…”
Section: Pendahuluanunclassified
“…In the Chinese culture context, the paternalistic leadership style is more conducive to corporating management of employees. At the same time, some studies point out that paternalistic leadership style is more conducive to enterprise management in collectivist countries (Koçak & Küçük, 2021;Nal & Sevim, 2020).…”
Section: Introductionmentioning
confidence: 99%